Cannabinoid receptor activation reverses kainate-induced synchronized population burst firing in rat hippocampus - Mason, Rob; Cheer, Joseph F. (Frontiers in Integrative Neuroscience, 2009)
Cannabinoids have been shown to possess anticonvulsant properties in whole animal models of epilepsy. The present investigation sought to examine the effects of cannabinoid receptor activation on kainic acid (KA)-induced epileptiform neuronal excitability. Under urethane anesthesia, acute KA treatment (10 mg/kg, i.p.) entrained the spiking mode of simultaneously recorded neurons from random firing to synchronous bursting (% change in burst rate). Injection of the high-affinity cannabinoid agonist (-)-11-hydroxy-8-tetrahydrocannabinol-dimethyl-heptyl (HU210, 100 µg/kg, i.p.) following KA markedly reduced the burst frequency (% decrease in burst frequency) and reversed synchronized firing patterns back to baseline levels. Pre-treatment with the central cannabinoid receptor (CB1) antagonist N-piperidino-5-(4-clorophenyl)-1-(2,4-dichlorophenyl)-4-methyl-3-pyrazole-carboxamide (rimonabant, SR141716A 3 mg/kg, i.p.) completely prevented the actions of HU210. The present results indicate that cannabinoids exert their antiepileptic effects by impeding pathological synchronization of neuronal networks in the hippocampus.